Queen Victoria: An Anatomy in Dress. (September 2019) - Storey, Matthew; Worsley, Lucy
Abstract : This object-based study of Victoria's surviving wardrobe uses dress as material evidence for the changes that took place to the Queen's physical body. Our exploration of the Queen's attitude towards clothing combined with her physical measurements as recorded in surviving items from her wardrobe allow us to nuance the conventional biographical narrative of a woman who consistently gained weight over her lifetime. We challenge the perception that she immediately became rotund after her husband's death as a consequence of grief and argue that her later-life mourning clothes were a distinctive, comfortable and rational response to her physical body and her status as a widow.